Production collaboration in the theatre : guiding principles - Bonds, Rufus Jr; Cominis, Maria; Ramont, Mark (Routledge, 2022)
"Production Collaboration in the Theatre reveals the ingredients of proven successful collaborations in academic and professional theatre training, where respect, trust, and inclusivity are encouraged and roles are defined with a clear and unified vision. Garnering research from conversations with over 100 theatre professionals on Broadway and in Regional and Educational Theatre, the authors provide multiple approaches to working together that are designed to help students and teachers of theatre discover and develop the collaborative tools that work best for them. Each chapter offers practical application with discussion prompts from real-life scenarios to practice and develop critical problem-solving skills necessary for theatre artists to navigate common collaboration challenges. Compelling topical case studies and insightful interviews invite readers to explore the principles of collaboration and inspire them to build joyful, equitable, and collaborative relationships in academic and professional settings. Production Collaboration for the Theatre offers theatre faculty and students a practical approach to developing interpersonal skills necessary for a lifetime career in collaborating in the theatre. An ideal resource for actors, directors, designers and production teams, this book provides theatre artists in training with an opportunity to develop their collaborative style that will guide and support the longevity of a successful career"--